Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Kompensasi Terhadap Produktivitas Kerja (Studi Perkebunan Sawit Kalimantan Barat) - Muhammad Rizky Nur Hanif; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted at an Oil Palm Plantation in Sanggau Regency. This oil palm plantation is an oil palm plantation which was once an empty land that was never used. Now, the vacant land has been converted into oil palm plantations. Maju Jaya Plantation has a production of less than 500 tons per year. This study aims to determine whether factors such as compensation, investment motivation, and work environment affect productivity. The method of distributing questionnaires is the type of research used. The sample of this study consisted of 42 respondents, and the data processing used the SPSS computer program. The variables used in this study are work efficiency (dependent variable), while the autonomous factors are workplace, work inspiration and salary. The validity and reliability requirements have been met by this study. Classical assumption take a look at, more than one linear regression, hypothesis testing, and data determination coefficient analysis were used in this study. The research findings show that work productivity is influenced by the work environment, employee motivation, and compensation. Scientists can further add various factors that can affect work efficiency, for example, work discipline, hard work attitude, preparation, etc. To examine the work environment, work motivation, and work productivity compensation on a larger scale, in terms of sample size and type of company, additional research is needed. Keywords: Work environment, work motivation, compensation, work productivity.